The devil is here in these hills West Virginia's coal miners and their battle for freedom - Green, James R. 1944- (Atlantic Monthly Press, 2015)
From before the dawn of the 20th century until the arrival of the New Deal, one of the most protracted and deadly labor struggles in American history was waged in West Virginia. On one side were powerful corporations whose millions bought armed guards and political influence. On the other side were 50,000 mine workers, the nation's largest labor union, and the legendary "miners' angel," Mother Jones. The fight for unionization and civil rights sparked a political crisis verging on civil war that stretched from the creeks and hollows to the courts and the US Senate. In The Devil is Here in These Hills, celebrated labor historian James Green tells the story of West Virginia and coal like never before